THE ROLE OF FAMILY EDUCATION IN ANTICIPATING TEENAGE DELINQUENCY IN MEKARSARI VILLAGE, CILAWU DISTRICT, GARUT REGENCY - Supriadi; Tetep (Journal Civics And Social Studies, 2024)
The problem of juvenile delinquency is an actual theme that a lot of the talk among parents, educators, religious social institutions and even governments. Teens often get stuck and deeds are always considered true regardless of other people and the environment. In this phase teenagers start searching for identity or identity. To prevent the occurrence of acts of delinquency committed by juveniles, it requires the participation of the attention of parents as educators in the family, so that teenagers can behave well. Based on the above problems, the authors conducted the study titled "The Role of Family Education In Anticipating Delinquency In the village Mekarsari Cilawu District of Garut". Formulation of the problem in this research is: "how the educational role of the family in anticipation of juvenile delinquency in the village Mekarsari Cilawu District of Garut". The hypothesis of this study is that if implemented with good family education, the juvenile delinquency in the village Mekarsari Cilawu District of Garut can be anticipated. The method used in this study: a descriptive analysis by observation, questionnaires, interviews, literature, and documentation. The population in this study were all heads of families and community leaders in the village of the District Mekarsari Cilawu. While sampled are 50 families and 10 community leaders. The findings of this study: educational role of the family in anticipation of juvenile delinquency categorized as high. . Keywords: Role of Family Education, Anticipate Delinguency